2006
DOI: 10.1111/j.1600-0838.2006.00562.x
|View full text |Cite
|
Sign up to set email alerts
|

Decreased shoulder function and pain common in recreational badminton players

Abstract: The aim of this study was to describe the prevalence and consequences of painful conditions in the shoulder region in recreational badminton players. A questionnaire study was performed on 99 players, of whom 57 were also assessed with Constant score. Previous or present pain in the dominant shoulder was reported by 52% of the players. Sixteen percent of the players had on-going shoulder pain associated with badminton play. A majority of these players reported that their training habits were affected by the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
30
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 26 publications
3
30
0
1
Order By: Relevance
“…Many archers did not admit having shoulder pain though they had positive clinical signs. Players ignoring the shoulder pain and continuing with the game has been observed in other games (7,9) as well. 21.11 % archers experienced the constant pain and most of them had experienced previous episodes of shoulder pain.…”
Section: Discussionmentioning
confidence: 90%
“…Many archers did not admit having shoulder pain though they had positive clinical signs. Players ignoring the shoulder pain and continuing with the game has been observed in other games (7,9) as well. 21.11 % archers experienced the constant pain and most of them had experienced previous episodes of shoulder pain.…”
Section: Discussionmentioning
confidence: 90%
“…The effects of certain personal and professional factors on shoulder pain such as sex, age, BMI, years of practice, job satisfaction, and level of sport have been investigated in other studies (eg, 12,23,[25][26][27]. In a descriptive epidemiologic study of shoulder injury in 59 top level English male volleyball players, Wang and Cochrane 25 reported that physical characteristics such as age, height, body weight, and weekly training hours did not appear to be risk factors for shoulder pain.…”
Section: Discussionmentioning
confidence: 98%
“…Fahlstrom and Soderman 26 determined the prevalence of shoulder pain in 99 recreational and championship badminton players, reporting no correlation between age and occurrence of shoulder pain. 26 Both studies had some methodological flaws including small sample size. 25,26 The prospective study of Miranda et al 27 evaluating the effects of work-related and individual factors on the incidence of shoulder pain reported that higher age increased the risk of shoulder pain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous or present pain in the dominant shoulder was reported by 52% of recreational badminton players, [105] and in a survey of world class players showed that previous or present shoulder pain on the dominant side was reported by 52% of the players. [106] Previous shoulder pain was reported by 37% of the players and ongoing shoulder pain by 20% of the players.…”
Section: Shoulder Pain and Sportmentioning
confidence: 99%